Taxonomic notes on the Indian whip scorpions (Arachnida: Thelyphonida) - Kayal, Mrinmoy Kumar; Sen, Souvik (Zootaxa, 2026)
Thelyphonids are a little-explored group of arachnids in India. The present study aims to provide a comprehensive taxonomic account of four whip scorpion species reported from India along with their current distribution map. Lectotypes are designated for Hypoctonus stoliczkae Gravely, 1912 and Uroproctus assamensis (Stoliczka, 1869) in order to stabilize their taxonomic identity.